2017
DOI: 10.2147/dddt.s129586
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interactions between glimepiride and rosuvastatin in healthy Korean subjects: does the <em>SLCO1B1</em> or <em>CYP2C9</em> genetic polymorphism affect these drug interactions?

Abstract: To improve cardiovascular outcomes, dyslipidemia in patients with diabetes needs to be treated. Thus, these patients are likely to take glimepiride and rosuvastatin concomitantly. Therefore, this study aimed to evaluate the pharmacokinetic (PK) interactions between these two drugs in healthy males and to explore the effect of SLCO1B1 and CYP2C9 polymorphisms on their interactions in two randomized, open-label crossover studies. Glimepiride was studied in part 1 and rosuvastatin in part 2. Twenty-four participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…OATP1B1 has a role in the transport of a wide variety drugs, such as statins. Several pharmacogenetic studies and metaanalyses have focused on the potential contribution of SLCO1B1 variations in the response to statins or repaglinide, but little attention has been paid to whether SLCO1B1 is involved in lipoprotein transformation and metabolic process that affects individual lipid levels [4][5][6][7][8][9][10][11][12][13][14][15]. We therefore hypothesised that common variants of SLCO1B1 have an impact into levels of serum lipids, and so by extension, a potential role in risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…OATP1B1 has a role in the transport of a wide variety drugs, such as statins. Several pharmacogenetic studies and metaanalyses have focused on the potential contribution of SLCO1B1 variations in the response to statins or repaglinide, but little attention has been paid to whether SLCO1B1 is involved in lipoprotein transformation and metabolic process that affects individual lipid levels [4][5][6][7][8][9][10][11][12][13][14][15]. We therefore hypothesised that common variants of SLCO1B1 have an impact into levels of serum lipids, and so by extension, a potential role in risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kim et al demonstrated a well-planned and meticulously executed clinical investigation to understand the role of SLCO1B1 or CYP2C9 genetic polymorphism on the pharmacokinetics of glimepiride and rosuvastatin in healthy Korean subjects 4. Most importantly, the pharmacokinetic interaction study consisted of two parts: parts 1 and 2.…”
mentioning
confidence: 99%
“…Recently, Kim et al demonstrated a well-planned and meticulously executed clinical investigation to understand the role of SLCO1B1 or CYP2C9 genetic polymorphism on the pharmacokinetics of glimepiride and rosuvastatin in healthy Korean subjects. 4 Most importantly, the pharmacokinetic interaction study consisted of two parts: parts 1 and 2. Part 1 was designed to evaluate the effect of rosuvastatin on the pharmacokinetics of glimepiride and part 2 was designed to determine the effect of glimepiride on the pharmacokinetics of rosuvastatin.…”
mentioning
confidence: 99%
See 2 more Smart Citations